EFEKTIVITAS PENGGUNAAN SUMBER BELAJAR BERBASIS MULTI MEDIA TERHADAP HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI KELAS VII SMP SWASTA ERIA TAHUN PELAJARAN 2019/2020 KECAMATAN MEDAN KOTA - Suhardi, Suhardi (Fakultas Agama Islam, 2020)
This study aims to determine the use of multimedia as a medium of Islamic Religious Education learning, Islamic Religious Education learning outcomes after using interactive multimedia, and the effect of the use of interactive multimedia on Islamic Religious Education learning outcomes for Class VII Students of ERIA Private Middle School, Medan Kota District. To get this data, the population is all Grade VII students of the ERIA Private Middle School 2019/2020 Academic Year, Medan Kota District. A total of 57 students. The sample is set by all students of class VII. In answering the problem of this research, the method used is quantitative / descriptive method. Data collection instruments in the form of a multimedia questionnaire as a source of learning and test results of Islamic Religious Education learning outcomes. The data analysis technique was using descriptive correlative study analysis technique. The hypothesis is tested using a questionnaire. Based on the results of this research can be seen the use of multimedia as a source of student learning classified into high categories with an average value of 69.82.